2013
DOI: 10.5194/bg-10-4297-2013
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term thermo-erosion of ice-rich permafrost coasts in the Laptev Sea region

Abstract: Permafrost coasts in the Arctic are susceptible to a variety of changing environmental factors all of which currently point to increasing coastal erosion rates and mass fluxes of sediment and carbon to the shallow arctic shelf seas. Rapid erosion along high yedoma coasts composed of Ice Complex permafrost deposits creates impressive coastal ice cliffs and inspired research for designing and implementing change detection studies for a long time, but continuous quantitative monitoring and a qualitative inve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
225
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 201 publications
(255 citation statements)
references
References 62 publications
(62 reference statements)
11
225
0
1
Order By: Relevance
“…This proportion is consistent with observations made by Günther et al (2013a), who find recent rates are at least 1.6 times more rapid than historical TD and TA along Ice Complex coastlines throughout the Laptev Sea. They report that for a subset of sites TA accelerated from long-term −3.3 ± 1.2 m a −1 to −5.7 ± 1.2 m a −1 over the past few years.…”
Section: Historical and Current Erosion Developmentsupporting
confidence: 92%
See 4 more Smart Citations
“…This proportion is consistent with observations made by Günther et al (2013a), who find recent rates are at least 1.6 times more rapid than historical TD and TA along Ice Complex coastlines throughout the Laptev Sea. They report that for a subset of sites TA accelerated from long-term −3.3 ± 1.2 m a −1 to −5.7 ± 1.2 m a −1 over the past few years.…”
Section: Historical and Current Erosion Developmentsupporting
confidence: 92%
“…Günther et al (2013a) found that TD and TA along Ice Complex coasts are interconnected: TA is the limiting component for coastal thermo-erosion intensity on the longterm scale. TA also better reflects the overall land loss of the base area of the island.…”
Section: Coastline Changesmentioning
confidence: 96%
See 3 more Smart Citations